Eronda e la Musa giambica ipponattea: per l'interpretazione del Mimiambo 1 (con un Excursus sulle Siracusane di Teocrito) - Nicola Piacenza (Annali Online dell'Università di Ferrara. Sezione Lettere)
Herondas’ first mimiamb is read through four basic elements: the references to the goddess Demeter and the old woman Iambe, the allusions to Hipponax, the Homeric model and the contacts with the other Hellenistic poets, in particular Theocritus (in this context, a new interpretation of Idyll 15, 40-1 is given) and Callimachus. All these components lead us to a metapoetic interpretation of the mimiamb, that should be rightly considered – like mimiamb 8 - as a programmatic poem.